Fractionally Integrated Time-Varying Volatility under Structural Break: Evidence from Kuala Lumpur Composite Index - Chin Wen, Cheong; Zaidi, Isa; Abu Hassan Shaari , Mohd Nor (UNIV KEBANGSAAN MALAYSIA, 2008)
This article study the influences of structural break to the fractionally integrated time-varying volatility model in Malaysian stock markets from year 1996 to 2006. A fractionally integrated autoregressive conditional heteroscedastic (FIGARCH) model combines with sudden changes of volatility is develops to study the possibility of structural change in Asian financial crisis and currency crisis. Our empirical results evidence substantially reduction in long memory clustering volatility after the inclusion of sudden changes in the volatility. Finally, the estimation, diagnostic and model selection evaluations indicate that the fractionally integrated model with structural change is out-performed compared to the standard model.